A research agenda for ecosystem services in American environmental and land use planning. (February 2017) - BenDor, Todd K.; Spurlock, Danielle; Woodruff, Sierra C.; Olander, Lydia
Abstract: We assess pathways for integrating the ecosystem services concept into American land use and environmental planning. Ecosystem services are the beneficial products that functioning ecosystems provide to human society. Building on Ian McHarg's influential ecological planning work, we argue that ecosystem service-based planning frameworks may improve our understanding of the consequences of planned actions in urban-ecological systems. Using evaluations of four diverse and innovative comprehensive plans, we examine how ecosystem service information can enhance plan specificity, investment strategies, and prioritization for policy implementation. Finally, we present a research agenda for evaluating how the use of ecosystem services in planning could improve assessment and communication of planning tradeoffs and outcomes. Highlights: Ecosystem services (ES) are ecosystem functions that provide benefits to humans. We assess four diverse comprehensive plans, examining use of ES info and analysis. Plans use ES info, but stumble on stakeholder engagement and use in decision-making. We present a research agenda to evaluate the use of ES to improve planning.